Control of autoimmunity by "epitope theft". - Kranc, K; Taylor, A; Willcox, N; Fugger, L (2005)
We all possess T cells with autoaggressive potential. Knowledge of their regulation is crucial for elucidating pathogenetic pathways and designing effective treatments for autoimmune diseases. A novel mechanism of T-cell silencing--in an autoimmune model--has recently been identified and is termed "epitope theft". The "thieves" are naive CD8+ T cells, which apparently "steal" MHC-class-I-antigen complexes from antigen-presenting cells (APCs). The deprived APCs can no longer activate other potentially pathogenic naive CD8+ T cells that are specific for the same epitope. This phenomenon is a previously unrecognized antigen-specific mode of protection against autoimmunity.